2005
DOI: 10.1364/josaa.22.002060
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the color-opponent signals under changes of illuminant in natural scenes

Abstract: Illumination varies greatly both across parts of a natural scene and as a function of time, whereas the spectral reflectance function of surfaces remains more stable and is of much greater relevance when searching for specific targets. This study investigates the functional properties of postreceptoral opponent-channel responses, in particular regarding their stability against spatial and temporal variation in illumination. We studied images of natural scenes obtained in UK and Uganda with digital cameras cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 45 publications
4
93
0
Order By: Relevance
“…because pattern is widely thought to be encoded by achromatic vision (Stoddard and Stevens 2010). Ferret luminance was taken as the L cone sensitivity (L-cones outnumber S-cones 14:1 (Calderone and Jacobs 2003)), human luminance was taken as (L+M)/2 (Lovell et al 2005), and peafowl luminance was taken as double cone sensitivity (Hart 2002). Luminance distribution differences (Luminance diff ) were calculated by comparing absolute differences in counts of the numbers of pixels in each target (plover egg or adult nightjar plumage) to its background at 32 linear levels of luminance (lum) from 0% to 100%:…”
Section: Image Processingmentioning
confidence: 99%
“…because pattern is widely thought to be encoded by achromatic vision (Stoddard and Stevens 2010). Ferret luminance was taken as the L cone sensitivity (L-cones outnumber S-cones 14:1 (Calderone and Jacobs 2003)), human luminance was taken as (L+M)/2 (Lovell et al 2005), and peafowl luminance was taken as double cone sensitivity (Hart 2002). Luminance distribution differences (Luminance diff ) were calculated by comparing absolute differences in counts of the numbers of pixels in each target (plover egg or adult nightjar plumage) to its background at 32 linear levels of luminance (lum) from 0% to 100%:…”
Section: Image Processingmentioning
confidence: 99%
“…Our prediction was that warning signals are often red, orange, or yellow, because these colors have higher contrasts than colors such as blue or white against green natural backgrounds, maximizing their conspicuousness (Endler, 1992;Endler and Mappes, 2004;Stevens and Ruxton, 2012). Illuminant spectra are known to vary with time of day and atmospheric conditions (Lovell et al, 2005;Nieves et al, 2012). Short wavelengths are expected to be less stable than longer wavelengths as atmospheric particles and cloud cover alter the contribution of Rayleigh-scattered sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that color opponency evolved as a mechanism to detect important components of a visual scene (Lovell et al, 2005). Such mechanisms can maximize the perception of color contrast, where achromatic information is unreliable due to spatial and temporal variation: for example ripe fruit against leafy backgrounds (Mollon, 1989;Maximov, 2000;Lovell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations